Neighborhoods and Food Insecurity in Households with Young Children: A Disadvantage Paradox?. (15th March 2017) - Denney, Justin T; Kimbro, Rachel Tolbert; Sharp, Gregory
Abstract: In the United States, more than 1 in 5 households with children are unable to access and provide adequate food for a healthy, active lifestyle. We argue that the contribution of local context for food insecurity risk has largely been overlooked in favor of focusing on individual family characteristics, and that this is problematic given that mitigating food insecurity may be a communal process. We examine the relevance of neighborhood contributors to food insecurity among children, utilizing geocoded and nationally-representative data from the ECLS-K: 2010-2011 kindergarten cohort. We find little evidence that neighborhood socioeconomic, food retail, or social services characteristics directly impact food insecurity risk. However, our results reveal that family and neighborhood socioeconomic characteristics combine to impact food insecurity in ways consistent with a disadvantage paradox. As neighborhood concentrated disadvantage increases, higher-SES families' risk of food insecurity increases, but lower-SES families' risk decreases. This paradox is not explained by a higher concentration of social service organizations in more disadvantaged neighborhoods, and we theorize that impoverished families with children may share information and resources in disadvantaged communities to avoid food insecurity.